How to Stimulate Innovation by Africa’s Private Sector - Broadman, Harry G. (International Finance Corporation, Washington, DC, 2018)
Governments in advanced economies have historically helped spur commercial innovation, particularly as a result of spillovers from defense related research and development. In many emerging markets, however, government lacks the resources or capabilities to do so. In Africa, as in other emerging markets, this has created an opening for private firms to drive innovation. By applying advances in technologies, businesses are enhancing productivity and growth across the continent.